Issues Connected with Auditing the Financial Statements of Healthcare Units - Chluska , Jolanta (Studia Oeconomica Posnaniensia, 2014)
The financial statements of healthcare units are audited by statutory auditors. The auditing principles for the financial statements of healthcare units should take into account the specific internal and external conditions of their functioning. The basic problems connected with their auditing include: a) assessing the feasibility of continuing operations, b) valuing the assets, c) assessing the financial condition of the unit. Despite certain problems, auditing the financial statements of healthcare units plays an important role in the authentication of the information included in the financial statements for the purpose of making economic decisions.